Sussing merger trees: the influence of the halo finder - Avila, Santiago; Knebe, Alexander; Pearce, Frazer R.; Schneider, Aurel; Srisawat, Chaichalit; Thomas, Peter A.; Behroozi, Peter; Elahi, Pascal J.; Han, Jiaxin; Mao, Yao-Yuan; Onions, Julian; Rodriguez-Gomez, Vicente; et al. (Oxford University Press, 2014)
Merger tree codes are routinely used to follow the growth and merger of dark matter haloes in simulations of cosmic structure formation. Whereas in Srisawat et. al. we compared the trees built using a wide variety of such codes, here we study the influence of the underlying halo catalogue upon the resulting trees. We observe that the specifics of halo finding itself greatly influences the constructed merger trees.We find that the choices made to define the halo mass are of prime importance. For instance, amongst many potential options different finders select self-bound objects or spherical regions of defined overdensity, decide whether or not to include substructures within the mass returned and vary in their initial particle selection. The impact of these decisions is seen in tree length (the period of time a particularly halo can be traced back through the simulation), branching ratio (essentially the merger rate of subhaloes) and mass evolution. We therefore conclude that the choice of the underlying halo finder is more relevant to the process of building merger trees than the tree builder itself. We also report on some built-in features of specific merger tree codes that (sometimes) help to improve the quality of the merger trees produced.